Management of patients with metastatic prostate cancer (mPC) in a rural part of North Norway with a scattered population: does living near the department of oncology translate into a different pattern of care and survival? - Nieder, Carsten; Dalhaug, Astrid; Haukland, Ellinor Christin; Norum, Jan (International Journal of Circumpolar Health, 2019)
Source at https://doi.org/10.1080/22423982.2019.1620086. The goal of the Norwegian Ministry of Health and Care Services is to offer an equal health-care service with the same outcomes wherever people are living within the country. The aim of this study was to evaluate whether this was true for patients diagnosed with metastatic prostate cancer (mPC) and living in Nordland County, a region with a challenging geography and climate and having, several small and remote communities and only 1 department of oncology. The latter is located in the main city, Bodø. We also compared a subgroup living in communities having lower average annual income (less than NOK 240,000 (equivalent to USD 28,600)) with patients living in Bodø (NOK 285,000 (USD 33,900)). Overall 288 patients were included and stratified into 3 subgroups (favourable distance and income, unfavourable distance and income, and unfavourable distance and favourable income). No statistically significant differences were observed regarding patient characteristics. There was no indication towards under-treatment among patients from the distant regions or the lower income region. Given that disparities were not observed, it was not surprising to see comparable survival outcomes (p=0.35). In conclusion, these results suggest that the health-care system in Nordland County successfully delivers state-of-the-art oncology care to patients with mPC.